Manajemen Strategi Orang Tua Mendidik Anak Menjadi Penghafal al-Qur’an dan Belajar Bahasa Arab Sejak Usia Dini di Nagari Pasar Tapan - Fananda, Yogi; Pohan, Muhammad Munawir; Anwar, Khairul (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2021)
Based on the results of research the author found that people's strategiesparents in improving children's memorization is by always respecting memorization children and provide motivation to children and control children and memorize it, give appreciation and gifts to the child, include the child in Tahfizd house for studying and memorizing the Koran and supporting factors parents in improving children's memorization, namely the parents themselves, their willand strong determination from the child, the right method, a conducive environment,supporting facilities, guidance from tahfizd teachers.